2017
DOI: 10.1038/s41598-017-00491-3
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of prognostic factors for survival after surgery for gallbladder cancer based on a Bayesian network

Abstract: The factors underlying prognosis for gallbladder cancer (GBC) remain unclear. This study combines the Bayesian network (BN) with importance measures to identify the key factors that influence GBC patient survival time. A dataset of 366 patients who underwent surgical treatment for GBC was employed to establish and test a BN model using BayesiaLab software. A tree-augmented naïve Bayes method was also used to mine relationships between factors. Composite importance measures were applied to rank the influence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 29 publications
7
22
0
Order By: Relevance
“…Clinicopathological variables, including IHC markers, were analyzed by multiple correlations test in a logarithmic multinomial model in order to assess independency between the variables. In accordance with a previous report by Cai et al, [15] we found that only tumor infiltration was significantly associated with median survival (Table S2). Next, we performed univariate analysis to stratify patients according to tumor infiltration grade.…”
Section: Nuclear Expresion Of Yap1 Correlated With Poor Prognosis In supporting
confidence: 93%
“…Clinicopathological variables, including IHC markers, were analyzed by multiple correlations test in a logarithmic multinomial model in order to assess independency between the variables. In accordance with a previous report by Cai et al, [15] we found that only tumor infiltration was significantly associated with median survival (Table S2). Next, we performed univariate analysis to stratify patients according to tumor infiltration grade.…”
Section: Nuclear Expresion Of Yap1 Correlated With Poor Prognosis In supporting
confidence: 93%
“…This result is consistent with the conclusions from previous studies [1,22]. The AJCC TNM stage is an important indicator for judging the degree of tumor progression, choosing treatment options, and determining prognosis [10,23]. In our results, the AJCC T stage and AJCC M stage were considered to be independent prognostic factors.…”
Section: Biomed Research Internationalsupporting
confidence: 93%
“…For differentiation grade, the nomogram demonstrated that N stage was a strong risk factor for M1. Reginal lymph node metastasis (N1) always indicates a worse prognosis among GBC patients [17,18], and several studies claim that N1 patterns are significant predictors of distant metastasis [19,20]. Our study further confirmed this finding, even among early stages of GBC.…”
Section: Discussionsupporting
confidence: 86%